Effects of the ankle angle on the electromyographic activity of the trunk and lower extremities during isometric squat exercises - Zhe Cui; Ying-Ying Tang; Myoung-Kwon Kim (Journal of Men's Health, 2022)
Background: Life in modern society has become convenient, but the lack of exercise due to a sedentary lifestyle has led to muscle weakness. The quadriceps femoris is essential for walking, standing, and using stairs in daily life. Muscle weakness can lead directly to impaired function. Squatting is the most representative exercise for effective muscle development and increasing the knee extensor strength. This study examined the effects of ankle angle during wall squats on the muscle activity of the vastus medialis oblique (VMO), vastus lateralis (VL), rectus femoris (RF), biceps femoris (BF), rectus abdominis (RA), and erector spinae (ES) to determine which ankle angle can better strengthen the vastus medialis oblique as a method of rehabilitation training after a knee joint injury. Methods: All subjects (n = 20) performed the following three types of wall squats randomly: (1) GWS (General Wall Squat), (2) WSD 10° (Wall Squat with dorsiflexion 10°), and (3) WSP 10° (Wall Squat with plantarflexion 10°). Each subject completed all three kinds of wall squatting exercises three different times, and the muscle activity data of the VMO, VL, RF, BL, RA, and ES were recorded. Results: Compared to GWS exercise, the VMO and RF muscle activity increased significantly under WSP 10° exercise (p < 0.05), whereas the VL, BF, RA, and ES activity did not increase significantly (p > 0.05). No significant change between WSD 10° and WSP 10° was observed (p > 0.05). Conclusions: WSP 10° can help increase the quadriceps muscle activity. Wall squat exercise with different ankle angles can be used for quadriceps muscle strengthening training for normal people and for recovery training for patellofemoral pain syndrome (PFPS) patients in the rehabilitation stage.